Perancangan Perencanaan Layanan Sistem Informasi Studi Kasus Unit B.A.U (Biro Administrasi Umum) di STMIK dan Politeknik LPKIA - Rismayadi, Danny Aidil (Sekolah Tinggi Manajemen Informatika dan Komputer PalComTech, 2019)
General administration bureau has the main task and function of preparing a plan, coordinating, directing and evaluating the implementation of activities in it as well as formulating technical policies in the fields of administration, governance, staffing and equipment based on legislation that applies as work guidelines. The General Administration at STMIK & Politeknik LPKIA is not only a center for administrative services, but also includes seven other important functions. Seeing the many functions that are so vital, the existence of a reliable information system service becomes inevitable. In developing and planning information systems in the General Administration. This study uses the Enterprise Architecture Planning method to document every part that focuses on business processes, data, applications and technology. The application of the User Generated Content method is also expected to reduce repetitive processes that cause waste of resources. The final result of this study is to produce an Integrated Information System that suits the needs of the institution, can contribute to the efficiency of costs and resources used, and produce an integrated information system service plan master plan that can be a reference for developing the current system.Keyword — General Administration, Enterprise Architecture Planning, User Generated Content, Masterplan.